Ferroptosis and its role in osteoarthritis: mechanisms, biomarkers, and therapeutic perspectives - Lu, Shanyu; Liu, Zhenyu; Qi, Meiling; Wang, Yingchao; Chang, Le; Bai, Xiaolong; Jiao, Yingguang; Chen, Xinyao; Zhen, Junping (Frontiers in Cell and Developmental Biology, 2024)
Osteoarthritis (OA) is one of the leading causes of disability worldwide, characterized by a complex pathological process involving cartilage degradation, synovial inflammation, and subchondral bone remodeling. In recent years, ferroptosis, a form of programmed cell death driven by iron-dependent lipid peroxidation, has been recognized as playing a critical role in the onset and progression of OA. Investigating the molecular mechanisms of ferroptosis and its involvement in OA may offer novel strategies for diagnosing and treating this disease. This review first outlines the core mechanisms of ferroptosis, with a particular focus on the roles of critical molecules such as Glutathione Peroxidase 4 (GPX4), Transferrin Receptor 1 (TfR1), and Nuclear Receptor Coactivator 4 (NCOA4). Subsequently, this study examines the specific impacts of ferroptosis on the pathophysiology of OA. Building on this, the potential of ferroptosis-related biomarkers for OA diagnosis and treatment is highlighted, along with proposed therapeutic strategies targeting ferroptosis regulation. This review aims to deepen the understanding of ferroptosis mechanisms and advance the clinical application of regulatory therapies for OA.